Multimodal Coherent Anti-Stokes Raman Scattering Microscopy With a Supercontinuum All-Fiber Laser - Yan Li; Xiaosheng Xiao; Jingjing Guo; Kangjun Zhao; Shunyu Yao; Lili Gui; Changxi Yang (IEEE Photonics Journal, 2019)
We demonstrate a compact supercontinuum (SC) all-fiber laser source for multimodal coherent anti-Stokes Raman scattering (CARS) microscopy based on an Er-fiber seed. It can be used in both high-speed narrowband CARS microscopy and broadband CARS spectroscopy at tens of milliseconds per pixel, by simply switching without realignment. The common pump pulses, generated from the SC in a highly nonlinear fiber (HNLF), are obtained after spectral filtering. The central wavelength of pump pulses is 1067.2 nm with a bandwidth of 0.8 nm, which provides a high-spectral resolution (<10 cm–1). By combining with the narrowband Stokes beam, which is directly obtained from the Er-fiber oscillator around ∼1550 nm, we can achieve a narrowband CARS microscopy in frequency shifts of ∼2700 to ∼3200 cm–1. The SC Stokes beam in a broadband CARS spectroscopy ranging from 1150 to beyond 1700 nm is generated in an HNLF, with vibrational spectra over a bandwidth of more than 2800 cm–1. We also analyzed the influences of different HNLFs on the SC generation both in simulation and experiment. The capability of our system in a multimodal CARS microscopy is demonstrated by the CARS detection of polystyrene and pork.